2014
DOI: 10.1007/s12032-014-0986-4
|View full text |Cite
|
Sign up to set email alerts
|

AEG-1 is associated with tumor progression in nonmuscle-invasive bladder cancer

Abstract: Astrocyte elevated gene-1 (AEG-1), a novel oncoprotein, has been implicated in oncogenesis and cancer progression in various types of human cancers. Here, immunohistochemistry was used to detect AEG-1 expression in nonmuscle-invasive bladder cancer (NMIBC), and these data were examined for correlation with clinicopathological parameters, and prognosis. Immunohistochemical analysis revealed that AEG-1 expression was significantly higher in bladder cancer tissues than that in normal tissues. High expression of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…MTDH, also known as astrocyte elevated gene-1, is first discovered in human foetal astrocytes in 2002 (41). MTDH is a multifunctional oncogene and overexpressed in multiple types of human cancer, including glioma (42), breast cancer (43), gastric cancer (44), colorectal cancer (45), cervical cancer (46) and bladder cancer (47). MTDH is correlated with tumorigenesis and tumour development by regulating cell groWTh, cell cycle, apoptosis, metastasis, epithelial-to-mesenchymal transition, chemoresistance and angiogenesis (48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…MTDH, also known as astrocyte elevated gene-1, is first discovered in human foetal astrocytes in 2002 (41). MTDH is a multifunctional oncogene and overexpressed in multiple types of human cancer, including glioma (42), breast cancer (43), gastric cancer (44), colorectal cancer (45), cervical cancer (46) and bladder cancer (47). MTDH is correlated with tumorigenesis and tumour development by regulating cell groWTh, cell cycle, apoptosis, metastasis, epithelial-to-mesenchymal transition, chemoresistance and angiogenesis (48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…5a and Supplementary Tables S4 and S5). Interestingly, Metadherin (MTDH) (also referred to as AEG-1 and “Protein LYRIC”), which has previously been shown to be up-regulated in BC and associated with BC progression 43, 44 , was significantly associated with LINC00958. Using Western blotting, we confirmed the physical association between MTDH and LINC00958 in the pull-down samples.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified the MTDH protein in the nucleus as well as the cytoplasm depending on the examined cell types 54 . However, in BC the up-regulated MTDH protein is primarily found in the cytoplasm 44 . Nevertheless further analyses are required to elucidate the mechanisms of action and functional role of the MTDH-LINC00958 association (as well as the other associations identified in the RIP analysis).…”
Section: Discussionmentioning
confidence: 98%
“…10 Moreover, the expression level of AEG-1 has been found to correlate with the clinical stage, differentiation degree, tumour grade, tumour metastasis, and survival time of patients. 3,[5][6][7][11][12][13][14][15] As a multifunctional gene, AEG-1 plays important roles in tumour growth, metastasis, angiogenesis, and drug resistance, thus contributing to tumorigenesis. [16][17][18][19][20] The expression level of AEG-1 is aberrantly high in melanoma.…”
mentioning
confidence: 99%